(3JQTjO GdEfaGb GdYGe(B/s - (3YQaGJ GdJgGei EHQGgjes; (3YGWa UObi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 1984)
(3JJfGhd GdHGMK ef NdGd GdHMK ehVhY JQTjO GdGfaGb GdYGe hJfGhd ef NdGd GdHMK fWGb GdMGLGJ GdYGeI hXGgQI JRGjO GdfabGJ GdYGeI aJfGhd GdJYQjaGJ GdeNJdaI ddMGLGJ GdYGeI hGdTQhW GdhGLH JhGaQgG dci Jchf GdMGLI MGLI YGeI (B. (3hjJYQV GjVG dXGgQI JRGjO GdfabGJ GdYGeI MjK jJYQV ddbGfhf GdYGe ddXGgQI aj HYV GdOhd GdeJbOeI hGdfGejI hCSHGH gPG GdJPGjO hbGe HOQGSI GdLOhi GdGLJeGYjI deTGQjY GdYGeI dJbjjegG hGdebGQfI HjfgG dGNJjGQ eTQhY eG Gh YOI eTGQjY ef Hjf GdeTGQjY GdeJfGaSI hPdc HGSJNOGe fXGe JMdjd GdJcdaI hGdYGFO hbGe HOQGSI JQTjOI GdfabGJ GdYGeI HGSJNOGe ehGRfI GdQbGHI hehRGfI GdHQGeL hGdGOGA hehGRfI GdJNWjW hGdHQeLI(B.s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B1984.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI UaMGJ(B: 453 - 491.s
Keywords: (3GdeGdjI GdYGeI hGdJTQjY GdVQjHjs; (3GdMGLGJ GdYGeIs; (3GdfabGJ GdYGeIs; (3GdefGaY GdaQOjIs; (3GdMGLGJ GdGLJeGYjIs; (3GdCYHGA GdYGeIs; (3GdMGLGJ GdLOjQI HGdETHGYs; (3GdehGRfI GdYGeI ddOhdIs; (3ehGRfI GdQbGHIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs